LIFESTYLE AND SELF-ESTEEM OF GENERATION Z IN GADGET PURCHASING DECISION - Sutanto, Eddy Madiono; Aubelia, Stela (TRIKONOMIKA, 2022)
The consumer purchasing decision is one of the essential aspects for companies to assess the success of their products. Lifestyle and self-esteem can cause consumer purchasing decisions. This study aimed to find the dependencies between lifestyle and self-esteem with the decision to purchase gadgets by Generation Z. The type of research was quantitative research with a judgmental sampling technique. The samples were 100 respondents who had purchased a gadget at least once. This study used questionnaires to collect data and processed the chi-square test by SPSS 2.5. The results showed that lifestyle and self-esteem had a positive dependency relationship on consumer purchasing decisions.